Problema Pembelajaran Pendidikan Agama Islam di Perguruan Tinggi - Hartinawanti H; Maria Ulfah Ashar; Syarifuddin Ondeng; Syahruddin Usman (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Islamic Religious Education (PAI) learning at General Higher Education Institutions (PTU) has a strategic role in shaping the character, moral, and spiritual of students amid the development of science and technology. However, its implementation still faces various problems, both in terms of learning methods, curriculum, lecturer competence, and digitalization development. This article aims to analyze various problems of PAI learning at PTU and offer strategic solutions to improve learning effectiveness. The method used is a literature study with a descriptive analytical approach through the review of various scientific literature and related research results. The results of the study indicate that PAI learning is still dominated by conventional approaches centered on lecturers, a curriculum that is less contextual, low utilization of digital technology, and a weak religious academic culture on campus. In addition, the development of social media and the flow of globalization also affect students' motivation to learn religion. Therefore, curriculum reform, innovation in student-centered learning methods, improvement of lecturer competence, integration of digital technology, and strengthening of a religious campus environment are needed so that PAI learning becomes relevant, interactive, and able to shape students who are characterized and have integrity in the modern era.